Optimizing Management of the Central Nervous System in Patients with Acute Lymphoblastic Leukemia Undergoing Allogeneic Stem Cell Transplantation - Pranalee Patel, BS; Mairead Dillon, BS; Donna Niedzwiecki, PhD; Mitchell E. Horwitz, MD; Chris R. Kelsey, MD (Advances in Radiation Oncology, 2023)
Purpose: To evaluate clinical outcomes and patterns of failure, specifically in regards to the central nervous system (CNS), in patients with acute lymphoblastic leukemia (ALL) undergoing allogeneic hematopoietic stem cell transplantation (HSCT) using total body irradiation (TBI)-based conditioning regimens. Methods and Materials: All adult patients (aged ≥18 years) with ALL undergoing allogeneic HSCT using TBI-based conditioning regimens treated from 1995 to 2020 at Duke University Medical Center were evaluated. Various patient, disease, and treatment-related factors were collected, including CNS prophylaxis and treatment interventions. Clinical outcomes, including freedom from CNS relapse, were calculated using the Kaplan-Meier method for patients with and without CNS disease at presentation. Results: One hundred and fifteen patients with ALL were included the analysis (myeloablative, 110; nonmyeloablative, 5). Of the 110 patients undergoing a myeloablative regimen, most (n = 100) did not have CNS disease before transplant. For this subgroup, peritransplant intrathecal chemotherapy was administered in 76% (median of 4 cycles) and 10 received a radiation boost to the CNS (cranial irradiation, 5; craniospinal, 5). Only 4 failed in the CNS after transplant, none of whom received a CNS boost, with freedom from CNS relapse at 5 years of 95% (95% confidence interval (CI), 84-98%). Freedom from CNS relapse was not improved with a radiation therapy boost to the CNS (100% vs 94%, P = .59). Overall survival, leukemia-free survival, and nonrelapse mortality at 5 years were 50%, 42%, and 36%, respectively. Among the 10 patients with CNS disease before transplant, 10 of 10 received intrathecal chemotherapy and 7 received a radiation boost to the CNS (cranial irradiation, 1; craniospinal, 6) and none subsequently failed in the CNS. A nonmyeloablative HSCT was pursued for 5 patients because of advanced age or comorbidities. None of these patients had prior CNS disease or received a CNS or testicular boost, and none failed in the CNS after transplant. Conclusions: A CNS boost may not be necessary in patients with high-risk ALL without CNS disease undergoing a myeloablative HSCT using a TBI-based regimen. Favorable outcomes were observed with a low-dose craniospinal boost in patients with CNS disease.